Improvement of The Procurement Delivery Time in PT Len Industri (Persero) - Novryadin, Nauzie; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2012)
One of the problems facing today in PT Len Industri is the speed in the procurement of goods. Based on procurement data in 2009 to 2011 there is an increase of time delays in the procurement delivery in that 3 years.To find the root cause of the problems faced, we used the CRT (Current Reality Tree) method. As there is no sufficient quantitative data, to find the root cause, more qualitative assessment were used, based on key stakeholder experience, through interview and discussion session. From the CRT method we found 9 (nine) root causes.There are several alternatives that could be used as solutions to overcome the root cause. The alternatives are divided into 3 (three) parts, namely the Procedure & Process (Simplification of procedures and Control Card & Form), Human Resources (Improve the HR capability and Recruitment for New Employee ) and Information System (Information systems Improvement and E-procurement).Implementation plan of the solutions offered above is divided to three following periods short term, medium term and long term. With the total cost of the improvement plan of Rp. 213.6 million and could be removed the potential fines between Rp. 19.6 million per day up to Rp. 35.3 million per day, it is time for the management of PT Len Industri to undertake corrective action to procurement system as proposed by this Final Project Keywords: Procurement, Delivery Time, CRT, e-Procurement